Effective Waste Management as a Predictor of Competitive Advantage: Mediating Role of Green Purchasing and Logistics - Chayanan Kerdpitak; Witthaya Mekkham; Luedech Girdwichai (International Journal of Supply Chain Management, 2019)
Nowadays organizations are facing intensive competition regardless of the industry and scale of operations. Globalization has also heightened the competition between the firms. On the other hand the rising global environmental issues have also created a tough environment for organizations as they are already focusing to gain the competitiveness. The study has attempted to study the impact of effective waste management on the competitive advantage. While the study has also considered the green supply chain practices as a potential mediator. The data were collected from the employees working in manufacturing companies in Thailand. The findings revealed a positive association between waste management and competitive advantage. Further findings also revealed that green logistics and purchasing acts as a mediator between relationships of waste management and competitive advantage. The future direction are provided at the end of research paper.